Structural Modeling of Fear of Intimacy Based on Object Relations with the Mediating Role of Splitting Emotional Conflict in Individuals Aged 25 to 50 - Asgharnia, Leila; Hamzehpoor Haghighi, Tahereh; Khasmohammadi , Mahdi; Pordelan, Nooshin (Mental Health and Lifestyle Journal, 2025)
The objective of this study was to examine the structural relationship between object relations and fear of intimacy, with the mediating role of splitting emotional conflict, in adults aged 25 to 50 years. This research employed a descriptive–correlational design using structural equation modeling (SEM). The statistical population included individuals aged 25–50 years who referred to counseling centers and psychology clinics in Tehran in 2023. A purposive and convenience non-random sampling method was used to select 300 participants who met the inclusion criteria. Data were collected using the Fear of Intimacy Scale (Descutner & Thelen, 1991), the Bell Object Relations Inventory (Bell, 1995), and the Self-Criticism/Self-Attack/Self-Reassurance Scale (Gilbert et al., 2004). Reliability and validity of the measures were confirmed, and data were analyzed using IBM SPSS version 27 for descriptive statistics and SmartPLS version 3 for SEM analysis. The results indicated that object relations significantly predicted splitting emotional conflict (β = 0.762, t = 22.282, p < 0.01) and fear of intimacy (β = 0.748, t = 21.799, p < 0.01). Splitting emotional conflict also significantly predicted fear of intimacy (β = 0.757, t = 22.105, p < 0.01). Furthermore, the indirect effect of object relations on fear of intimacy through splitting conflict was 0.576, and the total effect was 1.080, both statistically significant. Goodness-of-fit indices confirmed adequate model fit (R² = 0.586, GOF = 0.577, Q² = 0.238, NFI = 0.956). The findings suggest that dysfunctional object relations influence fear of intimacy both directly and indirectly through splitting emotional conflict, emphasizing the importance of early relational schemas and defense mechanisms in adult relational functioning. These results highlight the relevance of targeting object relations and splitting conflict in therapeutic interventions aimed at reducing intimacy fears and improving interpersonal relationships.